Bacterial Meningitis Score as Clinical Prediction Rule in Children with Acute Meningitis - Km, Roma; Shah, Gaurav Jung; Sah, Shyam Nandan (Journal of Nepalgunj Medical College, 2022)
Introduction: The early presentation of bacterial meningitis and aseptic meningitis are similar however treatment and outcome are different. The Bacterial Meningitis Score helps to differentiate bacterial meningitis from aseptic meningitis. Aims: To evaluate bacterial meningitis score as clinical prediction rule in children with acute meningitis. Methods: This was a hospital based prospective study done at pediatric department of Nepalgunj Medical College, Nepalgunj, a tertiary care reference hospital in Nepal, conducted from September 2020- August 2021. All the patients who were suspected of meningitis during the study period between the ages of 29 days to 15 years were included in this study. Results: A total of 138 patients were included in our study with 86 patients as aseptic meningitis and 52 patients as bacterial meningitis. Taking cut-off point of bacterial meningitis scoreto be 1.5 it’s sensitivity and specificity was found to be 100%. Area under ROC curve was found to be 1 showing 100% predictivity of bacterial meningitis score . The outcome of aseptic meningitis group was significantly better than bacterial group. Conclusion: Bacterial meningitis had grave prognosis associated with high mortality. Bacterial meningitis score is helpful to differentiate aseptic meningitis from bacterial meningitis to plan appropriate management timely.